Enhanced heterogeneous activation of peroxydisulfate by S, N co-doped graphene via controlling S, N functionalization for the catalytic decolorization of dyes in water. (November 2018) - Ren, Xiaohua; Feng, Jinkui; Si, Pengchao; Zhang, Lin; Lou, Jun; Ci, Lijie
Abstract: 3D porous sulfur and nitrogen co-doped graphene aerogel has been fabricated by a facile one-pot process. Both experimental and theoretical studies have demonstrated that sulfur and nitrogen co-doping could synergistically enhance the catalytic performance for activating peroxydisulfate (PDS) compared to the original and N doped graphene aerogels. The ratio of sulfur/nitrogen in the aerogel can be controlled by regulating the additions of thiourea and urea sources, and the aerogel with the S/N ratio of about 1:2.5 shows a better catalytic effect due to more significant changes in the electrostatic potential and the surface charge distribution, as revealed by the theoretical simulations. The radical quenching tests indicated that both SO4 · - and ·OH radicals could be formed in the SN-rGO aerogel + PDS system and contribute most to RhB degradation. Graphical abstract: Image 1 Highlights: 3D porous graphene with regulable S N doping was fabricated by a one-pot process. S, N co-doping could synergistically enhance the catalytic performance. Low S and high N can induce more disturbances to the surface chemistry of graphene. SO4 · - and ·OH were the main radicals in oxidation decolorization of dye. S, N co-doped graphene catalyst shows great recyclability and stability.